1990
DOI: 10.1212/wnl.40.4.605
|View full text |Cite
|
Sign up to set email alerts
|

The intracarotid amobarbital procedure as a predictor of memory failure following unilateral temporal lobectomy

Abstract: We investigated the efficacy of the intracarotid amobarbital procedure to accurately predict post-temporal lobectomy anterograde amnesia. We presented items at 2 separate times during amobarbital assessment; both early and late item recall were decreased during the injection contralateral to seizure onset indicating sensitivity to bilateral temporal lobe dysfunction. Ten patients for whom follow-up neuropsychological assessment was available failed either the early or late item recognition portions of their am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 0 publications
1
52
1
Order By: Relevance
“…In contrast to our findings, Loring et al (31), who describe an IAP procedure similar to ours, found no difference between seizure onset groups following injection contralateral to the side of seizure onset. However, the Loring et al (31) study included a separate group of items presented sometime after the initial 8 objects.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, Loring et al (31), who describe an IAP procedure similar to ours, found no difference between seizure onset groups following injection contralateral to the side of seizure onset. However, the Loring et al (31) study included a separate group of items presented sometime after the initial 8 objects.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the Loring et al (31) study included a separate group of items presented sometime after the initial 8 objects. In addition, reported mean amobarbital dosages were higher in the Loring et al (31) study than in ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its ability to predict memory function following unilateral medial temporal lobe resection has been highly variable (Loring, Meador, Lee, Martin, & Huh, 1998;Jack, Nichols, Sharbrough, Marsh, & Petersen, 1988;Jack et al, 1989). This may be related, in part, to the inconsistent delivery of sodium amytal to medial temporal lobe structures during Wada testing.…”
Section: Angiography Resultsmentioning
confidence: 99%
“…Unexpectedly, 12 of 13 severely amnesic persons obtained nearperfect memory scores. Amnesia had no impact on the speech protocol.…”
mentioning
confidence: 89%